PENENTUAN DAN APLIKASI FORMULA PEREKAT NABATI DARI EKSTRAK KULIT KAYU MAHONI PADA LAMINASI KAYU JABON - Abdurachman; Adi Santoso; Rohmah Pari (Jurnal Penelitian Hasil Hutan, 2021)
The domestic need for phenolic-based wood adhesives is high, but the material is currently imported, then altenative adhesivesare needed. This paper studies the characteristics of mahogany tannins and effective formulation of alternative adhesives made frommahogany bark extracts of mixture tapioca flour and industrial flour as extender applied to composite or glued products. The barkof mahogany was cut to the size of 2 cm x 1 cm x 0.1 cm, extracted with hot water (70–80°C) with a ratio of 1:3 (w/w,material/water) for 3 hours with two repetitions. After extraction product was filtered, and the filtrate was copolymerized usingresorcinol and formaldehyde under alkaline and room temperature conditions to produce resin tannin resorcinol formaldehyde(TRF). The blend of tapioca flour and industrial flour (1:1, w/w) as an extender was used in the TRF application to manufacturecomposite products. The results showed that this mahogany bark liquid extract could be copolymerized to form a resin which thenapplied as a wood adhesive in a cold pressing process. The optimum adhesive formula was a mixture of 0.25 mol of resorcinol and1-mol formaldehyde, with a 15% extender, and a catalyst (NaOH 40%) of 4% of the total weight of the adhesive formulation.The characteristics of mahogany tannin adhesives resemble those of the exterior type phenolic group.